A SLAM method to improve the safety performance of mine robot. (December 2019) - Zhu, Daixian; Sun, Xiaoting; Liu, Shulin; Guo, Ping
Highlights: PF based on bio-group intelligent optimization is a new development direction. Propose an adaptive closed-loop firefly algorithm to optimize the PF SLAM algorithm. The New FA uses the particle weight to determine the direction of firefly's movement. Abstract: The positioning accuracy of mine mobile robot is one of the important factors to ensure its safety in the complex mine environment. To improve the positioning accuracy of the robot, the improved firefly algorithm is introduced into particle filter SLAM, and firefly position update is applied instead of particle resampling, Improved the firefly brightness formula, designed the firefly position update formula, and adjusted the parameters of the firefly algorithm adaptively, and closed - loop method is used to control the optimization of firefly particles, witch controlled the balance between ability of global optimization and local optimization. Experimental results show that the method in this paper makes the particle distribution more reasonable, which further improves the robot's positioning accuracy and ensures its safety in complex environment.